HALAL LABEL: IS IT IMPORTANT IN DETERMINING BUYING INTEREST? - Amalia Mustika Inong; Savitri Hendradewi; Heny Ratnaningtyas (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2021)
Abstract: The purpose of this study was to determine the effect of the halal label on Korean noodle food on the buying interest of adolescent consumers. The population in this study were teenagers in the city of Jakarta. The number of samples that were successfully processed were 100 teenagers as respondents using random sampling method. This research uses simple regression analysis analysis. Data collection techniques by distributing questionnaires to 100 adolescent respondents in Jakarta. The test results in this study found that the halal label on Korean noodle food had a significant effect on the buying interest of teenage consumers. Halal labels are the basis for purchasing decisions for teenage consumers to fulfill religious beliefs, with the presence of halal labels on Korean noodle foods, it can be ensured that the food consumed is of good quality and good for health, which pays attention to the ingredients. The implication of this research is for business people to consider adding halal labels to their products, especially if they are marketed in countries with a majority Muslim population. Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh label halal pada makanan mie Korea terhadap minat beli konsumen remaja. Populasi dalam penelitian ini adalah remaja di kota Jakarta. Jumlah sampel yang berhasil diolah adalah 100 remaja sebagai responden dengan menggunakan metode random sampling. Penelitian ini menggunakan analisis analisis regresi sederhana. Teknik pengumpulan data dengan menyebarkan kuesioner kepada 100 responden remaja di Jakarta. Hasil pengujian dalam penelitian ini menemukan bahwa label halal pada makanan mie Korea berpengaruh signifikan terhadap minat beli konsumen remaja. Label halal menjadi dasar keputusan pembelian konsumen remaja untuk memenuhi keyakinan agama, dengan adanya label halal pada makanan mie korea dapat dipastikan makanan yang dikonsumsi berkualitas baik dan baik untuk kesehatan, yang memperhatikan kandungan bahannya. Implikasi penelitian ini adalah bagi para pelaku bisnis harus mempertimbangkan penambahan label halal pada produknya, khususnya jika dipasarkan di negara yang mayoritas berpenduduk muslim.